Architectural characteristics of the inner courtyards for the heritage houses in the citadel of Kirkuk - Muhammed Yunus, Sumbul; Sabah Haseeb, Qubad (International Journal of Engineering and Technology, 2019)
The inner courtyards can be regarded as one of the most significant designing features of the heritage buildings in general and it can also be regarded as the significant feature of the residential buildings in particular. The designing thoughts of the residential buildings are based on using the central courtyards as a central point to achieve the principle of heading inwards. These inner courtyards have special features which achieves the needs and the requirements of its residents. The studies which include the archeological side and its heritage elements of the social environment give us a clear impression about the social lifestyle of these societies especially from the residential side and how to adapt with the weather. So, this research concentrates on studying the archeological characteristics through the element of the inner courtyards in the heritage houses in the Citadel of Kirkuk. Kirkuk is one of the northern provinces of Iraq, in Asia, and it has rich archeological sites especially the heritage houses but these sites are almost unknown because there are only few studies in archeology about them. Research problem: Studying the archeological characteristics of the inner courtyards in the heritage houses in the Citadel of Kirkuk. The goal of the research: To analyze and study the characteristics of the inner courtyards according to its type, shape, constituents and the functionality of these elements. The research also aims to conduct a practical application on five chosen houses from the Citadel of Kirkuk.It was found that the architectural characteristics of the inner courtyards in the castle buildings are characterized by their high importance as a space overlooking the living spaces, and an integral nature connected to the cluster of the distributed to the neighboring spaces and takes up 25% of the housing area. The methodology of the research includes the method of description and analysis in the knowledge and exploration of the characteristics of internal courtyard of the heritage houses in the citadel of Kirkuk, by relying on the indicators derived from the previous studies and methods of measurement and analysis, to reach the research objectives where the architectural characteristics of the inner courtyard.